Informacyjny nadmiar i niedobór – dylematy edytora dramatów Żeromskiego. (Rzecz o Sułkowskim i Ponad śnieg bielszym się stanę) - Legutko, Grażyna (Poznańskie Studia Polonistyczne. Seria Literacka, 2016)
The article presents the problems faced by a modern editor of Stefan Żeromski’s dramas. In the case of the drama „Sułkowski” an editor has at their disposal extremely rich material enabling a detailed editorial commentary (connected with the origin of the drama, the historical sources used by Żeromski, subsequent stages of working on the text, publishing history, etc.), they do not however have the possibility to describe the original final draft of Sułkowski because it has not endured. In the case of „Ponad śnieg bielszym się stanę” (“Whiter Than Snow Shall I Be”), an editor does not have any concrete information which would show the birth of the idea of the drama and would give the testimony of working on the text; the editor does not also have any information about the first printing. Although the lack of extratextual information makes carrying out a critical editing of „Ponad śnieg bielszym się stanę” (“Whiter Than Snow Shall I Be”) more difficult, the endured original final draft and several pages of drama do recompense it in a way.